The Influence of Froth Height in Column Flotation of Kaolin Ore: An Advance Study - Fernando Pita (Current Advances in Chemistry and Biochemistry Vol. 8, 2021)
In froth flotation, the froth height, the entrainment and the drainage of particles affects recovery and grade. The aim of the froth phase is to transport all the hydrophobic particles that reach the pulp/froth interface into the floated and the drainage of the hydrophilic particles into the pulp. In this study, the influence of the froth height in the reverse flotation of kaolinitic ore was analyzed based on the recovery by entrainment and by true flotation of iron, titanium and manganese oxides (FeO, TiO2 and MnO). Also, the influence of the particle size in drainage process was analyzed. A successfully flotation process involves minimization of the entrainment and maximization of the true flotation. The recovery by entrainment and by true flotation of the three oxides is inversely proportional to the froth height. The entrained particles are drained easier in the froth phase than the floated particles, since they are not attached to the bubbles. The recovery by entrainment and drainage of the entrained material is similar for the three oxides. However, the recovery by true flotation and drainage of the floated material is different for the three oxides. For true flotation in the three oxides, the finest fraction presents smaller froth zone recovery. FeO has the lowest recovery, as consequence of the minor contribution of its hydrophobic minerals, while MnO has the greatest recovery values. For the entrained material, the finest fraction (<25 µm) is entrained easier, but it is also drained easier, meaning larger mobility of these particles in the froth zone. For the true floated material, the finest fraction (<25 µm) is drained easier indicating larger mobility of these particles in the froth; however, the coarsest fraction (>63 µm) is drained easier than the two intermediate fractions (+25-45 µm and +45-63 µm), indicating weaker attachment of the larger particles to the bubbles.